Mary’s Slave Song: The Tensions and Turnarounds of Faithfully Reading Doulē in the Magnificat - Lettsome, Raquel S. (Interpretation, 2021)
This article traces the enduring legacy of slavery in the United States and its biblical foundations that create interpretive tension around the Greek words doulos/doulē for readers and translators. Following Clarice Martin’s lead, I advocate for a faithful reading of doulē as “slave” in Luke 1:38, 48 and draw parallels between African-American slave songs and Mary’s Magnificat. I then explicate the tensions inherent in reading Mary as “the slave of the Lord” and “his [God’s] slave” against the socio-historical backdrop of U.S. slavery and explore how Mary’s slave song and narrative depiction by Luke “turns around” Mary’s slave language by reversing Orlando Patterson’s three constituent elements of slavery. When using this model, Luke transforms Mary’s slave language into a homeopathic practice and Mary into the embodiment of an African- American woman’s slave song.